2018
DOI: 10.1155/2018/9020914
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Neonatal Deaths in Ashanti Region of Ghana: A Cross-Sectional Study

Abstract: Background. Neonatal mortality continues to be a public health problem, especially in sub-Saharan Africa. This study was conducted to assess the maternal, neonatal, and health system related factors that influence neonatal deaths in the Ashanti Region, Ghana. Methods. 222 mothers and their babies who were within the first 28 days of life on admission at Mother and Baby unit (MBU) at the Komfo Anokye Teaching Hospital (KATH) in Kumasi, Ashanti Region of Ghana, were recruited through systematic random sampling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 17 publications
(24 reference statements)
3
33
3
Order By: Relevance
“…The odds of neonatal death was lower among female births compared with male births. This finding is in agreement with a study from Ghana [11], Nigeria [27], and Indonesia [28]. Accordingly, male neonates were at higher risk of death than female neonates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The odds of neonatal death was lower among female births compared with male births. This finding is in agreement with a study from Ghana [11], Nigeria [27], and Indonesia [28]. Accordingly, male neonates were at higher risk of death than female neonates.…”
Section: Discussionsupporting
confidence: 93%
“…According to different studies suggested there are many factors contributing to neonatal mortality. Among these: educational level [10], sex of the neonate, duration of pregnancy [11], home delivery without skilled provider [12], pregnancy complication [13], birth weight [14, 15], delay in seeking care during illness [16, 17], lack of preparedness of families and care providers, harmful cultural practices [18], economic status [19], social exclusion, maternal illiteracy [20], negative parental attitudes arising from the social environment, gender bias, inability to pay for care [20], and lack of basic prenatal, natal, and postnatal services [7, 21] were the main determinants of poor newborn survival rates in developing countries [2226].…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to low survival rate of preterm babies in Ghana and most developing countries. 27 Second, there is improved neonatal care in controlling complications of retinopathy of prematurity for those who survive.…”
Section: Discussionmentioning
confidence: 99%
“…According to [7] Sepsis in newborns can be hard to identify. Some of the symptoms in newborn babies may include but not limited to the following; Signs of distress during labor or delivery, such as a rapid heart rate, Changes in temperature (usually fever), breathing problems, such as very fast breathing, Digestive problems like poor appetite or an enlarged liver, Nervous system [8].…”
Section: Introductionmentioning
confidence: 99%